Social Rights, Judicial Remedies and the Poor - Octávio Luiz Motta Ferraz (Washington University Global Studies Law Review, 2019)
The increasing legal recognition of rights to health, education, and housing, often referred collectively as “welfare rights,” “social and economic rights,” or simply “social rights” as I shall refer to them in this piece, has generated heated debates on several interrelated questions. Are these rights of the same nature as other human rights such as freedom of speech, freedom of religion, freedom from torture, and fair trial, often collectively named “civil and political rights?” Should social rights be judicially enforced in exactly the same manner as civil and political rights? Who actually benefits when courts decide to enforce social rights assertively, the poor or the better-off? To repeat, these are interrelated questions. The nature of a right will influence the manner in which courts should enforce it or if they should enforce it at all. And the manner in which a court enforces a particular right, i.e., the type of remedy it chooses, may in turn have a significant bearing on who actually benefits from the right. To illustrate, those who believe that social rights are different in nature from civil and political rights tend to defend a less assertive role for courts when adjudicating them, or no role at all. This may in part be explained by a belief that, should courts use traditional rights protecting remedies, such as individualized injunctions, they might end up benefiting the “wrong” individuals, i.e., the better-off. On the other hand, those who believe that social rights and civil and political rights are identical in nature often, though not always, also believe that courts should therefore make no difference among them regarding enforcement. These debates are far from being purely academic, as they once were when social rights had been recognized in only a handful of constitutions and the United Nations International Covenant on Economic, Social and Cultural Rights (“ICESCR”) had been ratified by a dozen or so countries. With the increasing ratification of the ICESCR and other international law instruments that include social rights and the explosion in the number of national constitutions that include these rights, these debates have become more prominent and consequential. The debates left the constraints of academic circles and became the daily preoccupation of constitutional courts across the world, and, though less often, of international adjudicative bodies at the UN and regional human rights’ systems, such as those of Europe and Inter-America. My aim in this short commentary piece is not to describe and engage in detail with the several complex aspects of the important debates that flow from each of the questions above. Rather, I will focus on a specific aspect that has been the subject of renewed attention more recently: the issue of the distributive impact of judicial enforcement of social rights and its relationship with the type of remedy employed by courts when enforcing these rights. It has become increasingly clear in the experience of some countries that social rights’ judicial enforcement can often disproportionately benefit middle and upper classes rather than the poor. Some authors, such as David Landau and Pedro Felipe de Oliveira Santos have suggested that this is determined, in great part, by the type of remedies used by courts. If this is true, and assuming this is even a problem, the solution would logically lie at the remedial stage; that is, courts should adopt whatever remedies are most suited to achieve the desired result of benefiting the poor rather than the middle and upper classes. I want to suggest in this piece that the regressive effects of social rights litigation seem to me less related to the type of remedy than to the interpretation of social rights adopted by courts.
Keywords: social right; welfare right; social justice